China’s green finance and total factor energy efficiency - Zhou, Chaobo; Shaozhou, Qi; Yuankun, Li (Frontiers in Energy Research, 2023)
Based on 280 prefecture-level cities from 2008 to 2019, this study uses a difference-in-difference (DID) model to first analyze the impact of China’s green finance pilot policy (GFPP) on total factor energy efficiency (TFEE) and then further investigate the mediating and heterogeneous effects of GFPP. Results indicate that first, GFPP effectively improves TFEE, and the robustness tests show that the estimation results are reliable. Second, GFPP mainly improves TFEE by promoting industrial structure optimization and green technology innovation. Last, the role of GFPP in improving TFEE is mainly reflected in cities with high environmental protection enforcement and intellectual property protection. Therefore, China must expand the GFPP scope, further improve the local green finance practice capability, actively guide green fund to support energy technology innovation, accelerate green industrial transformation, and pool social forces to jointly promote green economic development.